Effect of Greenlight on the Growth Enhancement of Indian Major Carp in Bhopal, Madhya Pradesh - Sangma, Pearl Manapchi R; Minare, Anubhuti; Vyas, Vipin (AG Volumes, 2025)
The present study investigates the effect of green LED light exposure on the growth enhancement of Indian Major Carp (Labeo rohita) under controlled laboratory conditions. A 100-day experimental trial was conducted from September to November 2023 at the Department of Zoology and Applied Aquaculture, Barkatullah University, Bhopal (23.19894°N, 77.45225°E). Juvenile Labeo rohita were stocked in two fiber-reinforced plastic (FRP) tanks: one exposed to green LED light (520 nm) and another subjected to a standard photoperiod. Physico-chemical parameters such as temperature, dissolved oxygen (DO), pH, carbon dioxide (CO₂), and alkalinity were monitored weekly and remained within suitable ranges for carp culture. Fish were fed commercial floating pellets to satiation twice daily, and water was continuously aerated. Growth performance was assessed through regular measurement of fish length and weight. Initial length and weight of fish were 4 cm and 0.6 g, respectively. By the end of the experiment, fish reared under green light conditions exhibited slightly higher growth (final weight 1.25 g; length 6.05 cm) compared to those in the standard photoperiod tank (final weight 1.19 g; length 5.9 cm). Survival rates were also favorable, recorded at 92.5% in the green light tank and 88% in the control tank. The study indicates that green LED lighting can positively influence the growth and survival of Labeo rohita, making it a promising strategy for enhancing aquaculture productivity in controlled environments.